Water quality according to physicochemical variables and benthic macroinvertebrates in the Chucchun river micro-basin - Rodriguez Torres, Channel Yurico (2023)
The objective of this research is to compare the water quality between the physicochemical variables and the community of benthic macroinvertebrates in the Chucchun river micro-basin during the flood period of 2020. The Chucchun river runs through the section that is found in the three areas of the Huascarán Biosphere Reserve (nucleus, buffer and transition zone), likewise, is a water collection point for human consumption; Therefore, according to the ECAs for water, it is in category 1 (Population and recreational), A2: Water that can be made drinkable with conventional treatment. It was decided to analyze the water quality in nine sampling points, three points in each zone of the Biosphere Reserve, from the points of least to greatest interaction with human activities. The ICA determined results from EXCELLENT to GOOD and the IBA from VERY GOOD to GOOD, the values ​​in the indices decreased when there was greater interaction with human activity. Both indices were compared and a correlation of 86.87% was obtained, determining that as the river flows, the quality of the water decreases due to the socioeconomic activities carried out by the surrounding populations.